Making Mobile Browser Surveys Smarter: Results from a Randomized Experiment Comparing Online Surveys Completed via Computer or Smartphone. Issue 4 (November 2014) - Buskirk, Trent D.; Andrus, Charles H.
With nearly 50% of U.S. mobile phone subscribers using smartphones, survey researchers are beginning to explore their use as a data collection tool. The Got Healthy Apps Study (GHAS) conducted a randomized experiment to compare mode effects for a survey completed via iPhone mobile browser and online via desktop/laptop computer web browser. Mode effects were assessed for three types of outcomes: randomization/recruitment, survey process/completion, and survey items. In short, the distribution of survey completion times and the distribution of the number of apps owned were significantly different across survey mode after accounting for block group. Other key mode effects outcomes (including open-ended items, slider bar questions, and missing item rates) showed no significant differences across survey mode. Some interesting qualitative findings suggest that iPhone respondents enter more characters and omit fewer items than originally thought.